Designing a system to generate electricity from usual surrounding motions through piezoelectric to run surveillance systems on the port - Ahmed, Arian; Muyeed, Munyem Ahammad; Alve, Sheikh Sajid Ali; Chowdhury, Maher Mahmood Saif (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.